Clinical Sign for Missed Decompression of a Separate Extensor Pollicis Brevis Compartment in de Quervain’s Disease - Benatar, Niels (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2017)
Persistent pain despite previous surgery for de Quervain’s disease might be due to an overlooked septum between the abductor pollicis longus tendon slips and the extensor pollicis brevis tendon, or an overlooked completely separate compartment for the extensor pollicis brevis tendon alone. In both of these instances, extension of the MP joint of the thumb against resistance elicits pain at the distal level of the first extensor compartment of the wrist. When this sign is positive, revisional surgery and decompression of the remaining septum or separate compartment is indicated.
Keywords: de Quervain’s disease; separate extensor pollicis brevis compartment; incomplete release of first extensor tendon compartment